Disaster assistance: determinants of countries around the world contributing towards disaster donations - Wei, J.; Marinova, Dora; Zhao, D. (InderScience, 2014)
Foreign responses after Hurricane Katrina and the Wenchuan and Haiti earthquakes varied. The cluster analysis in this paper shows that 35 countries were preferentially US-oriented, 47 Haiti-oriented, 33 China-oriented, 33 had no explicit orientation and 32 did not offer assistance. Further evidence about geographies of generosity or geopolitical orientation was found, with the North American countries more likely to assist US and the Asian countries - China. Haiti however did not have any particular appeal to North America. The 33 countries found to implement a pure humanitarian approach to disaster aid have higher per capita gross domestic product (GDP) and general government consumption expenditure, indicating that foreign assistance depends on the state of the economy and larger public sector. A country with a higher human development index (HDI) is also more likely to donate. Finally, the paper argues the need for a global information network (GIN) to assist in coordinating disaster activities and improve communication channels.